Manajemen kelompok kerja guru berbasis efektivitas kinerja UPT Kecamatan Ngemplak Kabupaten Sleman - Susanto, Anang (Journal of Education Policy and Management Studies, 2024)
The aim of this research is to describe management of KKG based on affectivity in Gugus III Wedomartani, Ngemplak, Sleman. Management of KKG in Gugus III Wedomartani includes planning, implementation, and evaluation. Management of KKG Gugus III Wedomartani refers to standard development of KKG/MGMP that published by Ministry of National Education.This research uses qualitative approach namely case study. The data research which use description both orally and written gained from data collecting activity which is done using interview, observation, and documentation. The analysis of the data, the researcher uses three components, namely data reduction, data display, and conclusion drawing verification.The result of this research shows that management of KKG in Gugus III Wedomartani consist of program standard, organization standard, human resources standard, and funding standard. The implementation of KKG includes infrastructure standard, management standard and evaluation standard that consist of internal evaluation and evaluation of sub-district level. Based on the result of the research, the researchers suggest three points, namely: first, maximize the teamwork of organization and decrease the central figure of the organization. Second, make a more various routine program and development program. Third, bring the competent authorities outside to give a various suggestion which make KKG organization better.